Future Internet technologies for environmental applications. (April 2016) - Granell, Carlos; Havlik, Denis; Schade, Sven; Sabeur, Zoheir; Delaney, Conor; Pielorz, Jasmin; Usländer, Thomas; Mazzetti, Paolo; Schleidt, Katharina; Kobernus, Mike; Havlik, Fuada; Bodsberg, Nils Rune; et al.
Abstract: This paper investigates the usability of Future Internet technologies (aka "Generic Enablers of the Future Internet") in the context of environmental applications. The paper incorporates the best aspects of the state-of-the-art in environmental informatics with geospatial solutions and scalable processing capabilities of Internet-based tools. It specifically targets the promotion of the "Environmental Observation Web" as an observation-centric paradigm for building the next generation of environmental applications. In the Environmental Observation Web, the great majority of data are considered as observations. These can be generated from sensors (hardware), numerical simulations (models), as well as by humans (human sensors). Independently from the observation provenance and application scope, data can be represented and processed in a standardised way in order to understand environmental processes and their interdependencies. The development of cross-domain applications is then leveraged by technologies such as Cloud Computing, Internet of Things, Big Data Processing and Analytics. For example, "the cloud" can satisfy the peak-performance needs of applications which may occasionally use large amounts of processing power at a fraction of the price of a dedicated server farm. The paper also addresses the need for Specific Enablers that connect mainstream Future Internet capabilities with sensor and geospatial technologies. Main categories of such Specific Enablers are described with an overall architectural approach for developing environmental applications and exemplar use cases. Highlights: Future Internet technologies and its support for environmental applications. "Generic Enablers" leverage Future Internet technologies such as Cloud Computing, Internet of Things, and Big Data. "Specific Enablers" connect mainstream Future Internet capabilities with sensor and geospatial technologies. Demonstration of Generic and Specific Enablers at work in environmental applications.